2006
DOI: 10.1177/0002764206286563
|View full text |Cite
|
Sign up to set email alerts
|

Deciding the Future

Abstract: This study examines the retirement planfulness of men and women in dual-earner couples using data from the Ecology of Careers Study and structural equation modeling. It assesses whether each spouse plans independently, whether this is a gendered division of labor, whether both spouses' plans mutually influence each other, or whether decision making about retirement is an individual process for each member of a couple. The authors find that spouses' levels of retirement planfulness are positively related but in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Understanding these dynamics will require more research since it is likely that definitive generational differences can be confidently identified only by using longitudinal data tracking each generational group. Following Moen's work (Chesley and Moen, 2006; Moen et al , 2006), examining the life course of individuals and couples and looking at espoused attitudes as well as actual behaviors may provide additional insight into the nature of generational effects. Finally, generational cohort and family stage may interact with or moderate the differences in antecedents (and outcomes) of work‐family conflict and synergy.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding these dynamics will require more research since it is likely that definitive generational differences can be confidently identified only by using longitudinal data tracking each generational group. Following Moen's work (Chesley and Moen, 2006; Moen et al , 2006), examining the life course of individuals and couples and looking at espoused attitudes as well as actual behaviors may provide additional insight into the nature of generational effects. Finally, generational cohort and family stage may interact with or moderate the differences in antecedents (and outcomes) of work‐family conflict and synergy.…”
Section: Discussionmentioning
confidence: 99%
“…This warrants further investigation with more heterogeneous samples and might lead to implications not only for including the partner in intervention supporting the individual transition to retirement (Ahlers, 2004) but also for targeting interventions to different types of couples. For example, it has been reported that dual-earner couples often plan to retire together and cohort effects on the transition to retirement reflecting different realities regarding gender equality in the workforce (Moen et al, 2006;Ho and Raymo, 2009). Other studies have found that younger dual-earner couples do not generally prefer to retire jointly, only if they report high levels of relationship and low levels of work attachment (Eismann et al, 2017) and that perceived influence on retirement decisions by the partner yields ambivalent results calling for validating the need of the retirees for autonomy while including the partner in the retirement process (Smith and Moen, 2004).…”
Section: Aging Togethermentioning
confidence: 99%
“…In summary, retirement preparation among those employed influences income during old age. Moen, Huang, Plassmann, and Dentinger (2006) found in their study that spouses' decision making in the form of retirement planning tends to be positively related to what the respondents' retirement planning behaviour. A study conducted by HSBC (2008) revealed that only a small proportion of people will be prepared for retirement and be completely protected in terms of receiving adequate retirement income.…”
Section: Review Of Literaturementioning
confidence: 91%